Sport Marketing Mix Impact on Intention to Revisit Buriram - Watjanasoontorn, Itsra; Viriyasuebphong, Petcharut; Voraseyanont, Parameth (Journal of Thai Hospitality and Tourism, 2019)
Sports tourism is a tourism product which a destination can propose to the market. This is the growing trend of the recent tourism industry. The role of sport tourism has seen many in Europe. Therefore, many countries in Asia are also following this tourism trend to stimulate sports tourism as the destination choice. In the case of Buriram, Thailand is an example of a successful strategy to promote the province's interest as a sports tourism destination. This research study and examine sports marketing mix (7Ps) as factor impact domestics’ tourist intention to revisit Buriram. The data collection used primary data that are taken by spreading questionnaire to 400 domestics’ tourist. The 378 respondents were collected at I-mobile Stadium and Buriram Racing International Circuit (BRIC). The result showed key elements of the sports marketing mix; product, price, place, physical evidence, process, people and promotion mix which impact on domestics’ tourist intention to revisit sports tourism in Buriram. There are only five supported hypotheses (price, place, physical evidence, process, and promotion mix) that can be used to predict domestic’s tourist intention to revisit. The contribution of the study will be given due emphasis by sport tourism stakeholders; tour operators, hotels, restaurants, airlines, and local national government organizations that involved with tourism, especially in Buriram to sustain their tourist continual visit and the development of their events and services.